CHALLENGES IN THE EMC STANDARDIZATION OF WIRELESS POWER TRANSFER SYSTEMS - Jaekel, Bernd (Journal of Energy Technology, 2024)
Charging of electrical and electronic equipment is currently mostly done via conducted connection to an AC/DC power supply unit. However, trends in technology, also driven by issues of convenience for the user, are moving towards wireless power transfer (WPT). A wireless process, in which most of the power is just used for the transfer of energy, includes the usage of a frequency for the power transfer, hence needing resources in the frequency spectrum. As the frequency spectrum is more or less completely assigned to the usage of radio or other services, such as industrial, scientific or medical (ISM) applications, it turns out to be a relatively complex task to actually decide on which frequencies can be used for WPT technology. This paper describes the challenges in the determination of such frequencies in terms of standardization and presents the related consequences.